2021
DOI: 10.3389/fphar.2021.617678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pharmacist-Led Clinical Pathway/Order Sets on Cancer Patients: A Systematic Review

Abstract: Background: Pharmacist-led clinical pathways/order sets (PLCOs) were first applied for designated diseases and surgical operations, such as cancer. They were not used in pharmacotherapy until recently. After screening a large number of publications, we found that PLCOs were rarely accessible.Objective: To evaluate the effects and the changes of relevant medical outcomes of PLCOs.Methods: Articles from PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, Wanfang database, and China Biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The rationality of pharmacotherapy within these pathways is critical as it directly impacts treatment efficacy and patient safety, contributing to cost control ( 21 ). Pharmacists in the implementation process should provide optimal drug treatment plans based on clinical guidelines and latest research, overseeing drug interactions and side effects to ensure patient safety, and participating in drug selection with cost–benefit considerations ( 22 , 23 ). However, our study found that pharmacists interviewed were only partially involved in clinical pathways, like reviewing drug treatment plans, and faced challenges due to insufficient pharmaceutical knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The rationality of pharmacotherapy within these pathways is critical as it directly impacts treatment efficacy and patient safety, contributing to cost control ( 21 ). Pharmacists in the implementation process should provide optimal drug treatment plans based on clinical guidelines and latest research, overseeing drug interactions and side effects to ensure patient safety, and participating in drug selection with cost–benefit considerations ( 22 , 23 ). However, our study found that pharmacists interviewed were only partially involved in clinical pathways, like reviewing drug treatment plans, and faced challenges due to insufficient pharmaceutical knowledge.…”
Section: Discussionmentioning
confidence: 99%